Tension-Compression Damage Model with Consistent Crack Bandwidths for Concrete Materials - Wei He; Ying Xu; Yu Cheng; Peng-Fei Jia; Ting-Ting Fu (Advances in Civil Engineering)
This paper proposes a tension-compression damage model for concrete materials, formulated within the framework of thermodynamics of irreversible processes. The aim of this work is to solve the following problems: the premature divergence of numerical solutions under general loading conditions due to the conflict of tensile and compressive damage bounding surfaces, which is a result of the application of the spectral decomposition method to distinguish tension and compression, and the unsatisfactory reproduction of distinct tension-compression behaviors of concrete by strain-driven damage models. The former is solved by the sign of the volumetric deformation, while the latter is solved via two separated dissipation mechanisms. Moreover, of specific interest is an improved solution to the problem of mesh-size dependency using consistent crack bandwidths, which takes into account situations with irregular meshes and arbitrary crack directions in the context of the crack band approach. The performance of the model is validated by the well-documented experimental data. The simplicity and the explicit integration of the constitutive equations render the model well suitable for large-scale computations.